PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. TRANSCOM - Aisyah, Siti (www.bsi.ac.id, 2015)
The existence of the human resources in an enterprise is very important because of its existence with human resources largely determine whether or not a company forward. With the availability of human resources for the activities of the company will be well underway. To improve the performance of the employees of the company must provide the motivation of its employees in order to gain better employee performance and employee morale in the works. Influece motivation work the performance employess of PT. TRANSCOM 0.924 it doesn’t significantly 0.05and there is factor influence the performance employess of PT. TRANSCOM.Therefore it takes motivation of yourself or the environment, effect on performance results, in order to work more passion again and timely Keywords: work motivation, performance employees